ALLOCATION OF FUNDS FOR RURAL DEVELOPMENT (Study of Social Realization of Community Participation on Development in Gampong Merduati Village Banda Aceh) - Sukowati, Praptining; Usman, Muhammad; Weni, I Made; Sadhana, Kridawati (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to describe and analyze community participation and the factors that influence the development of the Gampong Merduati village in Banda Ace. The qualitative research method is the method used in this study. Determination of informants is done by purposive sampling, assuming that the informant understands the problem being studied and can provide information and responses to the problems that are the objectives of this study. The data needed in this study consists of primary data and secondary data. Data collection techniques in the field, namely through interviews, observation, and documentation studies. Data analysis in this study used the method of Milles and Hubernan (1984) which consisted of Data Reduction, Display Data, and Conclusion Drawings. The results of this study show that community participation in the implementation of the Village Fund Allocation (ADD) in the Gampong Merduati Banda Aceh, both participation in the form of energy, mind, and participation in the form of budget has been running well, in accordance with the wishes of community members and implementation instructions. Factors affecting community participation in the implementation of the Village Fund Allocation in Gampong Merduati Village in Banda Aceh are a sense of belonging, responsibility, and habits that have become a tradition in the Gampong Merduati Village. The ability of human resources (HR) of community members is reliable so that it has implications for the quality and quantity of the Village Fund Allocation itself. This research recommends further research on the role of government in encouraging community involvement in development.